Hybrid supercapacitors for reversible control of magnetism - Alan Molinari (Nature Portfolio, 2017)
The ability to electrically control magnetism could enable a new generation of low-power electronic devices. Here the authors show that charging and discharging of supercapacitors are powerful tools to achieve reversible above-room-temperature magnetoelectric effects.